Lietuvos istorijos bibliografiniai šaltiniai (XIX a.– 1940 m. laikotarpio darbų apžvalga) - Miežinienė, Ala (Knygotyra, 1972)
In the present article are shown the main trends and tendencies in the development of bibliography on the history of Lithuania and are reviewed the most important bibliographical works on the history of Lithuania published in Lithuania, Russia and in the Soviet Union from the beginning of the 19th century to 1940.Bibliographical sources on the history of the Lithuanian SSR published until 1940 are divided into two major groups:1) bibliographies on the history of Lithuania published until 1917, and 2) bibliographical sources on the history of Lithuania published during the period from 1917 to 1940. Such a division helps to connect the history of bibliography with the development of historical science, to reveal its connection with the main trends and tendencies of historiography and bibliography of that time, to ascertain scientific and social functions of historical bibliography, etc.The bibliography on the history of Lithuania has passed a long and complicated process of formation. The article shows its historical development depending on the concrete historiographical achievements of a certain period, on the scientific needs as well as on the class and political interests of the society. In various bibliographical sources abundant literature on the history of Lithuania has been registered, much experience in methods of bibliographing has been gained, all principal genres of historical bibliography have been promoted. Bibliographical sources on the history of Lithuania published from the beginning of the 19th century to 1940 are of great scientific and practical importance. Soviet bibliography on Lithuanian history leans upon the progressive and democratic traditions of the pre-socialist Lithuanian historical bibliography.